Increased activity of the antioxidants systems modulate the oxidative stress in saliva of toddlers with early childhood caries - Silva, Priscila Vieira Da [UNESP]; Troiano, Jéssica Antonini [UNESP]; Nakamune, Ana Cláudia de Melo Stevanato [UNESP]; Pessan, Juliano Pelim [UNESP]; Antoniali, Cristina [UNESP] (Elsevier, 2016)
Objective This study aimed to evaluate the oxidative stress levels and the enzymatic and non-enzymatic antioxidant systems in saliva of toddlers with severe early childhood caries (S-ECC). Design Unstimulated saliva samples were collected at the morning from 0 to 3 year-old S-ECC (n = 30) or caries-free (CF) children (n = 30/group) for evaluation of oxidative stress (OS) and total antioxidant capacity (TAC), which were measured by the ferric reducing antioxidant power (FRAP) assay, as well as to assess the activity of enzymatic (superoxide dismutase, SOD) and non-enzymatic (uric acid, UA) antioxidant systems, respectively. Data were analyzed by Student's t-test (p < 0.05). Results Significantly higher protein levels were observed in saliva of S-ECC children (0.083 mg/mL) than in the CF group (0.070 mg/mL). Oxidative damage was significantly lower in saliva of S-ECC children (0.0019 μmol/L/mg protein) than in CF children (0.0039 μmol/L/mg protein), while salivary TAC (61.5 μmol/L), SOD activity (36.6 UE/mL) and uric acid (7.05 mg/mL) were significantly higher in saliva of S-ECC when compared to the CF group (49.1 μmol/L, 26.8 UE/mL and 5.02 mg/mL, respectively for TAC, SOD and UA). Conclusion Oxidative stress levels were significantly lower in saliva of S-ECC children, what might be associated with the increased activity of salivary enzymatic (SOD) and non-enzymatic (uric acid) antioxidant systems.
Keywords: Children; Dental caries; Oxidative stress; Saliva; Superoxide dismutase; Uric acid